Salidroside inhibits melanin synthesis and melanoma growth via mTOR and PI3K/Akt pathways - Ouyang, Qi; Tian, Shengye; Zhou, Hengyu; Mao, Ying; Li, Xiang; Yan, Feng; Liu, Ailong; Hu, Xiang; You, Changqiao; He, Jun (Frontiers in Oncology, 2025)
BackgroundMelanomas are caused by the malignant transformation of melanocytes. Numerous studies have demonstrated that the tyrosol components of salidroside inhibit tyrosinase activity. The PI3K/Akt/mTOR signaling pathway plays a crucial role in biological pigment synthesis. However, how salidroside achieves its anti-melanoma effect in melanoma by regulating PI3K/Akt/mTOR remains poorly understood. This study aimed to explore the effect of salidroside on PI3K/Akt/mTOR in melanoma, which plays a role in regulating melanogenesis.MethodsNetwork pharmacology was predicted that salidroside may exert an anti-melanoma effect through modulating melanin synthesis functions and signaling pathways. Zebrafish whole-embryo in situ hybridization, RT-qPCR, melanin synthesis and tumorigenesis assays, and were performed to investigate the therapeutic efficacy of salidroside in melanin synthesis. The mechanism of salidroside in anti-melanoma activity was examined by RT-qPCR, Western blot, immunofluorescence, in vivo imaging, immunohistochemistry.ResultsWe confirmed salidroside may exert an anti-melanoma effect through modulating melanin synthesis-related gene expression and PI3K/Akt pathway by Network pharmacology. Furthermore, salidroside slowed melanin synthesis in zebrafish embryos and H2O2-induced B16F10 cells by inhibited oxidative stress. Moreover, we determined the effect of salidroside on anti-melanin synthesis via PI3K/Akt/mTOR pathway in vitro, and western blot results showed that salidroside increased the expression of Nrf2 in the nucleus, as well as inhibited the phosphorylation of mTOR and PI3K/Akt pathway. Finally, intratumoral administration showed salidroside suppressed melanoma growth.ConclusionSalidroside inhibits melanin synthesis and melanoma development most likely by its antioxidant properties and downregulating the PI3K/Akt/mTOR pathway. Our results may provide a novel therapeutic strategy for the treatment of melanoma.